Effect of FGF/FGFR pathway blocking on lung adenocarcinoma and its cancer‐associated fibroblasts. Issue 2 (24th June 2019) - Hegab, Ahmed E; Ozaki, Mari; Kameyama, Naofumi; Gao, Jingtao; Kagawa, Shizuko; Yasuda, Hiroyuki; Soejima, Kenzo; Yin, Yongjun; Guzy, Robert D; Nakamura, Yoshikazu; Ornitz, David M; Betsuyaku, Tomoko
Abstract: Cancer‐associated fibroblasts (CAFs) are known to promote tumourigenesis through various mechanisms. Fibroblast growth factor (FGF)/FGF receptor (FGFR)‐dependent lung cancers have been described. We have developed a mouse model of lung adenocarcinoma that was constructed through the induction of Fgf9 overexpression in type 2 alveolar cells. The expression of Fgf9 in adult lungs resulted in the rapid development of multiple adenocarcinoma‐like tumour nodules. Here, we have characterised the contribution of CAFs and the Fgf/Fgfr signalling pathway in maintaining the lung tumours initiated by Fgf9 overexpression. We found that CAF‐secreted Fgf2 contributes to tumour cell growth. CAFs overexpressed Tgfb, Mmp7, Fgf9, and Fgf2 ; synthesised more collagen, and secreted inflammatory cell‐recruiting cytokines. CAFs also enhanced the conversion of tumour‐associated macrophages (TAMs) to the tumour‐supportive M2 phenotype but did not influence angiogenesis. In vivo inhibition of Fgfrs during early lung tumour development resulted in significantly smaller and fewer tumour nodules, whereas inhibition in established lung tumours caused a significant reduction in tumour size and number. Fgfr inhibition also influenced tumour stromal cells, as it significantly abolished TAM recruitment and reduced tumour vascularity. However, the withdrawal of the inhibitor caused a significant recurrence/regrowth of Fgf/Fgfr‐independent lung tumours. These recurrent tumours did not possess a higher proliferative or propagative potential. Our results provide evidence that fibroblasts associated with the Fgf9‐induced lung adenocarcinoma provide multiple means of support to the tumour. Although the Fgfr blocker significantly suppressed the tumour and its stromal cells, it was not sufficient to completely eliminate the tumour, probably due to the emergence of alternative (resistance/maintenance) mechanism(s). This model represents an excellent tool to further study the complex interactions between CAFs, their related chemokines, and the progression of lung adenocarcinoma; it also provides further evidence to support the need for a combinatorial strategy to treat lung cancer. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.